Storytelling method using big book to improve children's listening skill - Sri Wahyuni; Suharni Suharni; Retanida Retanida (Universitas Ahmad Dahlan, 2020)
The low of listen ability in children aged 5-6 years is the background of this action research, so this research aims to improve these abilities. One method that has proven to be effective solve that problem is the method of storytelling with a big book. Data on classroom action research was collected using observation techniques and analyzed in quantitative descriptive. This study involved ten students as participants. The result of the study showed that storytelling with a big book can improve the listening skill of 5-6 years old children in PAUD Bintang Mutiara, Pekanbaru. Before applying storytelling method with big book, the participantsâ€™ listening skill was categorized as â€˜has not been developedâ€. After applying the storytelling method with big book, their listening skill was categorized as â€œDeveloped as expectedâ€ with a score of 71.67%. The improvement of participantsâ€™ listening skill from â€˜pre-cycleâ€™ to â€˜cycle 1â€™ was 21%. From cycle I to cycle II, their listening skill was improved by 64%. From pre-cycle to cycle II, the improvement was 89%. Overall, the improvement of listening skills was 75.56%.